2023
DOI: 10.1007/s40121-023-00805-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Respiratory Syncytial Virus in Adults Substantially Increases When Adding Sputum, Saliva, and Serology Testing to Nasopharyngeal Swab RT–PCR

Abstract: Introduction Nearly all existing respiratory syncytial virus (RSV) incidence estimates are based on real-time polymerase chain reaction (RT–PCR) testing of nasal or nasopharyngeal (NP) swabs. Adding testing of additional specimen types to NP swab RT–PCR increases RSV detection. However, prior studies only made pairwise comparisons and the synergistic effect of adding multiple specimen types has not been quantified. We compared RSV diagnosis by NP swab RT–PCR alone versus NP swab plus saliva, sputu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The proportions of all respiratory infections attributable to RSV in our study (3–4%) are also similar to previous observational studies, which reported that 4–8% of symptomatic respiratory infections in adults age ≥ 60 years were caused by RSV [ 14 , 63 ]. The relatively similar values from our model-based approach and prospective study estimates that have been adjusted for reduced sensitivity of nasal/nasopharyngeal swab PCR [ 16 , 17 ] in adults provide support for the validity of our model structure.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The proportions of all respiratory infections attributable to RSV in our study (3–4%) are also similar to previous observational studies, which reported that 4–8% of symptomatic respiratory infections in adults age ≥ 60 years were caused by RSV [ 14 , 63 ]. The relatively similar values from our model-based approach and prospective study estimates that have been adjusted for reduced sensitivity of nasal/nasopharyngeal swab PCR [ 16 , 17 ] in adults provide support for the validity of our model structure.…”
Section: Discussionsupporting
confidence: 54%
“…For the first time, RSV vaccines were recently licensed to prevent lower respiratory tract disease caused by RSV in adults ≥ 60 years [ 12 , 15 ]. Yet, the incidence and clinical burden of RSV disease in adults are difficult to measure due to the lack of specific RSV symptomatology that could distinguish it from influenza and other respiratory viruses, limited standard-of-care RSV testing among adults, reduced sensitivity of diagnostic testing among adults [ 16 , 17 ], poor RSV diagnostic capacity in many healthcare facilities, and low public and medical community awareness of RSV in adults [ 18 21 ]. Furthermore, data on RSV burden in people with underlying conditions are sparse [ 4 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of using saliva as a diagnostic tool for respiratory pathogens has gained widespread attention since being demonstrated as an acceptable and sensitive sample type for the detection of SARS-CoV-2 during the COVID-19 pandemic (Tobik et al, 2022). Adding to the global success of many saliva-based SARS-CoV-2 tests, a recent study by Ramirez et al (Ramirez et al, 2023) demonstrated the utility of saliva for RSV diagnosis. They observed that its inclusion alongside the gold-standard NPS resulted in a twofold increase in the diagnostic yield when compared to NPS alone.…”
Section: Discussionmentioning
confidence: 99%
“…24 In contrast, self-collectible samples like saliva and urine are cheaper and less invasive options requiring a fraction of the resources. 24 Combined with perceptions regarding the upper respiratory sample types, the acceptability of saliva may prove beneficial for diagnosing various infectious diseases, including SARS-CoV-2, MERS-CoV, Ebola, Zika, 23 influenza, 25 respiratory syncytial virus (RSV), 26 and more 27 in the developing world. 24 Several limitations exist in considering the broader applicability of the results in this study.…”
Section: Discussionmentioning
confidence: 99%